CircRNAs in Malignant Tumor Radiation: The New Frontier as Radiotherapy Biomarkers - Xixi Wu; Junying Wu; Junying Wu; Lingxia Wang; Wei Yang; Bo Wang; Huan Yang; Huan Yang (Frontiers in Oncology, 2022)
World Health Organization (WHO) data show that of the top 20 factors that threaten human life and health, cancer is at the forefront, and the therapeutic approaches for cancer consist of surgery, radiotherapy, chemotherapy and immunotherapy. For most highly metastatic and recurrent cancer, radiation therapy is an essential modality to mitigate tumor burden and improve patient survival. Despite the great accomplishments that have been made in clinical therapy, an inevitable challenge in effective treatment is radioresistance, the mechanisms of which have not yet been completely elucidated. In addition, radiosensitization methods based on molecular mechanisms and targets, and clinical applications are still inadequate. Evidence indicates that circular RNAs (circRNAs) are important components in altering tumor progression, and in influencing resistance and susceptibility to radiotherapy. This review summarizes the reasons for tumor radiotherapy resistance induced by circRNAs, and clarifies the molecular mechanisms and targets of action. Moreover, we determine the potential value of circRNAs as clinical indicators in radiotherapy, providing a theoretical basis for circRNAs-based strategies for cancer radiotherapy.